2011
DOI: 10.1007/s10530-011-0062-3
|View full text |Cite
|
Sign up to set email alerts
|

Fitness consequences of anthropogenic hybridization in wild red-legged partridge (Alectoris rufa, Phasianidae) populations

Abstract: Hybridization is a widespread phenomenon, which plays crucial roles in the speciation of living beings. However, unnatural mixing of historically isolated taxa due to human-related activities has increased in recent decades, favouring levels of hybridization and introgression that can have important implications for conservation. The wild redlegged partridge (Alectoris rufa, Phasianidae) populations have recently declined and the releases of farm-reared partridges have become a widespread management strategy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 43 publications
(76 reference statements)
0
44
0
2
Order By: Relevance
“…The BC area could represent an "extreme" and unsuitable habitat for hybrids, considering that individuals used to restock neighboring areas are for "put-and-take" partridge hunting (Byers and Burger 1979), with low chances of survival into the wild in the long term. However, in a wild population located in central Spain, Casas et al (2012) found that A. rufa x A. chukar hybrids may breed as well as or even better than "pure" redlegged partridges although their feeding behaviors result in a lower survival rate. Thus, the lower survival rate of hybrids could be compensated by their higher ability to hatch.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The BC area could represent an "extreme" and unsuitable habitat for hybrids, considering that individuals used to restock neighboring areas are for "put-and-take" partridge hunting (Byers and Burger 1979), with low chances of survival into the wild in the long term. However, in a wild population located in central Spain, Casas et al (2012) found that A. rufa x A. chukar hybrids may breed as well as or even better than "pure" redlegged partridges although their feeding behaviors result in a lower survival rate. Thus, the lower survival rate of hybrids could be compensated by their higher ability to hatch.…”
Section: Discussionmentioning
confidence: 97%
“…It is wellknown that captive-born birds are prone to difficulties in acclimatization due to adverse genetic and behavioral factors and that they are susceptible to health issues. These are reflected in a shorter survival compared to wild individuals, mainly through easy predation (Meriggi and Mazzoni della Stella 2004;Perez et al 2004Perez et al , 2010Alonso et al 2005;Casas et al 2012). The present study provides insights into the genetic structure of self-sustaining and expanding redlegged partridges living in two areas of NW Italy (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…rufa have decreased due to several factors like predation, problems related to the release of farmreared partridges (sanitary and hybridisation risks), deterioration of their natural habitat due to changes in land use, and increase of hunting pressure (Buenestado et al, 2009;Casas et al, 2012;Delibes-Mateos et al, 2012). Although it is known that releases of red-legged partridges raised under farming conditions do not contribute to an effective conservation of their wild populations and it may even be a threat to it (Negro et al, 2001;Pérez et al, 2004;Barbanera et al, 2010), A. rufa is raised in these countries for hunting purpose in order to ensure hunting bags and provide birds for re-establishment purposes (Sokos et al, 2008;Díaz-Fernández et al, 2012).…”
mentioning
confidence: 99%
“…Releases of farm-reared partridges can bring the introduction of new diseases and parasites (Villanúa et al 2008;Millán 2009;Díaz-Sánchez et al 2012) or genetic introgression due the release of hybrids between red-legged and chukar partridges (Blanco-aguiar et al 2008;Barbanera et al 2010;Casas et al 2012). Our study also indicates that it can also lead to overhunting of wild stocks, which can further contribute to the decline of partridge populations, especially in low-density populations (Blanco-Aguiar 2007).…”
Section: Discussionmentioning
confidence: 68%
“…García and M. Calero-Riestra, unpublished data). Similarly, we used blood samples to detect chukar partridge (A. chukar) introgression using nine DNA diagnostic markers (8 nuclear microsatellite loci + 1 mitochondrial PCR-RFLP locus on a cytochrome b sequence), following the procedures described in Casas et al (2012). We considered a bird as hybrid when at least one of the genetic markers showed introgression from chukar.…”
Section: Methodsmentioning
confidence: 99%